Targeting autophagy in pancreatic cancer: The cancer stem cell perspective - Troumpoukis, Dimitrios; Papadimitropoulou, Adriana; Charalampous, Chrysanthi; Kogionou, Paraskevi; Palamaris, Kostas; Sarantis, Panagiotis; Serafimidis, Ioannis (Frontiers in Oncology, 2022)
Pancreatic cancer is currently the seventh leading cause of cancer-related deaths worldwide, with the estimated death toll approaching half a million annually. Pancreatic ductal adenocarcinoma (PDAC) is the most common (>90% of cases) and most aggressive form of pancreatic cancer, with extremely poor prognosis and very low survival rates. PDAC is initiated by genetic alterations, usually in the oncogene KRAS and tumor suppressors CDKN2A, TP53 and SMAD4, which in turn affect a number of downstream signaling pathways that regulate important cellular processes. One of the processes critically altered is autophagy, the mechanism by which cells clear away and recycle impaired or dysfunctional organelles, protein aggregates and other unwanted components, in order to achieve homeostasis. Autophagy plays conflicting roles in PDAC and has been shown to act both as a positive effector, promoting the survival of pancreatic tumor-initiating cells, and as a negative effector, increasing cytotoxicity in uncontrollably expanding cells. Recent findings have highlighted the importance of cancer stem cells in PDAC initiation, progression and metastasis. Pancreatic cancer stem cells (PaCSCs) comprise a small subpopulation of the pancreatic tumor, characterized by cellular plasticity and the ability to self-renew, and autophagy has been recognised as a key process in PaCSC maintenance and function, simultaneously suggesting new strategies to achieve their selective elimination. In this review we evaluate recent literature that links autophagy with PaCSCs and PDAC, focusing our discussion on the therapeutic implications of pharmacologically targeting autophagy in PaCSCs, as a means to treat PDAC.